The Development of Animated Video Learning Media on Theme 7 Subtheme 2 Learning 1 in Grade IV SDN Tejo 1 Mojoagung - Nurul Fajriyah; Muhammad Nuruddin (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2022)
The use of learning media when in class can help students in understanding the material. Learning media is a means to deliver learning materials that can stimulate the mind and build students' interest in learning so that learning objectives can be achieved. For this reason, it is important to have learning media during teaching and learning activities. This research was conducted aimed at “ (1) knowing the process of developing animated video learning media Theme 7 Subtheme 2 Learning 1 Grade IV, (2) knowing the implementation of animation video learning media products Theme 7 Subtheme 2 Learning 1 Grade IV, (3) knowing student responses to the mediia of learning animated videos Theme 7 Subtheme 2 Learning 1 Grade IV”. The type of research used is development research. The development model used for the development of animated video learning media is the ADDIE model. There are 5 stages in this ADDIE model, namely: Analyze, Design, Develpoment, Implementation, Evaluation. The results of research that has been carried out show that this animated video learning media is very suitable for use in learning. From the validation results, animated video learning media obtained a percentage of 93.75% with the category of very valid or used without revision. From the results of the pre-test and posttest, student learning outcomes have increased after being tested for development products. From the student response questionnaire, it showed an average percentage of 84.58% with a very interesting category.